Improving Students' Learning Outcomes by Solving Open-Ended Problem in Highway Laboratory:Work in Progress - Muntasher, Khalida H.; Kittur, Javeed (Journal of Engineering Education Transformations, 2016)
The field of pavement design is dynamic due to the changes in increasing traffic and environmental conditions. The flexible pavement design concept has been selected for this study. The Highway laboratory and the Transportation Engineering courses are offered in the same semester. The paper aims at improving the students learning by carrying out an open - ended experiment in Highway Laboratory, a 1 credit mandate course at B. V. Bhommaraddi College of Engineering&Technology, Hubballi. The theoretical concepts are taught in the course 'Transportation Engineering' which is a 4 credit required course for all civil engineering students. This course provides an introduction to the various aspects of highway engineering, were the author focus is on the design of flexible pavement using mechanistic empirical approach. The work presented in this paper tests the students knowledge on the concept of pavement design by giving an online objective test. The students are assessed at two different stages, one being soon after the completion of theoretical concepts and other after the completion of the open - ended experiment. This work in progress study focuses on comparing the students' learning attainment after undergoing lecture based learning and project based learning. It is expected to have an increased attainment in students learning after performing the open - ended experiment.